Scottish Exceptionalism? Normative Codes of Scottish Nationalism in the British and EU Crises - Law, Alex (Cambio. Rivista sulle Trasformazioni Sociali, 2017)
Scotland has thus far proved immune to the appeal of right-wing populism present in many European neoliberal democracies. This paper argues that changing tension balances in the crises facing the UK as a union state cannot be reduced to an understanding of the supposedly internal challenge of Scottish sub-state nationalism. Instead sub-state nationalism needs to be situated in the shifting long-term, inter-state power balances of Britain as a union state and a rising and falling world power. Such an approach builds on the promise offered by the historical sociology of Norbert Elias to account for the over-functioning of the normative humanist we-ideals of Scottish civic nationalism in the British and EU crises.